Workshop Suply Chain Manajemen Untuk Meningkatkan Efisiensi Bisnis Dengan Menggunakan Aplikasi Moonsonsim Di SMA Wiyata Dharma - Loo, Petrus; Marpaung, Linda Wahyu (LPPM STIKOM Tunas Bangsa, 2024)
The constitution of teachers and lecturer (no14 of 2005) provides that teachers are professional educators and scientists with major assignments to transform, develop, and promote science, technology, and the arts through education, research, and community research. Public service (PKM) is a subjective duty, so it is compulsory. PKM is itself a direct process of implementation of science, technology and cultural arts using scientific methodologies as propagation of tri darma. In simple terms, PKM can be defined as implementation process or application of technologies and science to the public. This service to the public was performed at wiyata dharma high school in a workshop. PKM is planning to use monsoonsim using using monsoonsim to supply chain management. Where a supply chain management is an approach used to promote integration of suppliers, manufacturing, distirsions, retailer and custommer so that the products produced in the right amount, the right time and the right locations to minimize costs and give satisfaction to consumers can be very useful in helping students understand difficult concepts. This helps students to think systematically and logically as they progress through scenarios full of uncertainty and complexity.